1988
DOI: 10.1007/bf00019519
|View full text |Cite
|
Sign up to set email alerts
|

The Agrobacterium tumefaciens T-DNA gene 6b is an onc gene

Abstract: In this article it is shown that the T-DNA of Agrobacterium tumefaciens contains besides the well-known cyt and aux genes another gene with an oncogenic effect in plants. The gene in question is called 6(b) and causes the formation of small tumors in plant species such as Nicotiana glauca and Kalanchoe tubiflora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 14 publications
1
44
0
Order By: Relevance
“…Various phenotypic effects associated with the expression of 6b have been reported, as follows: (1) formation of tumors on certain plants (Hooykaas et al, 1988;Spanier et al, 1989;Tinland et al, 1989Tinland et al, , 1992; (2) stimulation of the ipt -induced and iaaM / iaaH -induced division of cells (Tinland et al, 1989(Tinland et al, , 1990Wabiko and Minemura, 1996); (3) reduction in the formation of shoots on leaf discs that is normally induced by appropriate levels of exogenous or endogenous cytokinin (Spanier et al, 1989); (4) generation of shoot-bearing calli on leaf discs on phytohormone-free medium (Wabiko and Minemura, 1996); (5) inhibition of the growth of Rol -induced hairy roots via the induction of an undifferentiated state and the formation of calli (Tinland et al, 1990); and (6) alterations in the morphology of leaves of transgenic tobacco plants that express the 6b gene (Tinland et al, 1992;Wabiko and Minemura, 1996). Although there are some discrepancies among previously reported results (Leemans et al, 1982;Ream et al, 1983), it is accepted generally that the product of 6b stimulates the proliferation of plant cells and affects the development of 1 Current address: National Institute for Basic Biology, 38 Nishigounaka, Myo-daiji-cho, Okazaki 444-8585, Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various phenotypic effects associated with the expression of 6b have been reported, as follows: (1) formation of tumors on certain plants (Hooykaas et al, 1988;Spanier et al, 1989;Tinland et al, 1989Tinland et al, , 1992; (2) stimulation of the ipt -induced and iaaM / iaaH -induced division of cells (Tinland et al, 1989(Tinland et al, , 1990Wabiko and Minemura, 1996); (3) reduction in the formation of shoots on leaf discs that is normally induced by appropriate levels of exogenous or endogenous cytokinin (Spanier et al, 1989); (4) generation of shoot-bearing calli on leaf discs on phytohormone-free medium (Wabiko and Minemura, 1996); (5) inhibition of the growth of Rol -induced hairy roots via the induction of an undifferentiated state and the formation of calli (Tinland et al, 1990); and (6) alterations in the morphology of leaves of transgenic tobacco plants that express the 6b gene (Tinland et al, 1992;Wabiko and Minemura, 1996). Although there are some discrepancies among previously reported results (Leemans et al, 1982;Ream et al, 1983), it is accepted generally that the product of 6b stimulates the proliferation of plant cells and affects the development of 1 Current address: National Institute for Basic Biology, 38 Nishigounaka, Myo-daiji-cho, Okazaki 444-8585, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the 6b gene might function in the activation and/or inactivation of cytokinin and auxin (Hooykaas et al, 1988;Spanier et al, 1989); it might increase and/or decrease the sensitivity of transformed cells to these plant hormones (Hooykaas et al, 1988;Tinland et al, 1989) by modifying putative hormone transport systems or reporters (Spanier et al, 1989); its product might interact with ipt and iaa genes and/or their products (Tinland et al, 1989) and/or it might stimulate signal perception systems (Wabiko and Minemura, 1996). It also has been proposed that the 6b gene might affect the concentration of endogenous plant hormones in transformed cells (Spanier et al, 1989).…”
mentioning
confidence: 99%
“…Infection with either gene leads to the formation of undifferentiated tumors on a limited number of host plants (Hooykaas et al, 1988;Otten and Schmidt, 1998). Similarly, overexpression of the KNAT2 and CycD3 genes causes an auxin-and/or cytokininindependent tumor formation on Arabidopsis leaves (Dockx et al, 1996;Riou-Khamlichi et al, 1999).…”
mentioning
confidence: 99%
“…However, conservation of 6b in the T-DNA regions of many Ti plasmids (Otten and De Ruffray, 1994) suggests a role for the gene in the neoplastic diseases caused by transformation with T-DNA. It has been proposed that the 6b gene might play a more critical role in tumorigenicity in certain specific species of the host plant (Hooykaas et al, 1988). If the efficiency of the formation of crown gall tumors depends on levels of expression of plant cell divisionrelated genes that might be supported by combinatorial functions of the products of the hormone-synthesizing genes from the T-DNA mentioned above and of 6b, which encodes a histone chaperone-like protein, 6b might play a more critical role in the formation of crown galls in host plants that are relatively insensitive to the actions of the phytohormones.…”
Section: Possible Roles Of 6b In the Formation Of Crown Gall Tumorsmentioning
confidence: 99%
“…Various hypotheses have been proposed to explain the effects of 6b on the growth of plant cells (Leemans et al, 1982;Ream et al, 1983;Hooykaas et al, 1988;Tinland et al, 1992;Wabiko and Minemura, 1996). This gene modulates the inductive effects of cytokinins on shoot development (Spanier et al, 1989); it interferes with the induction and elongation of roots in an auxindependent rolABC-based rooting assay, suggesting that 6b might reduce the effect of high levels of auxin to maintain cells in an undifferentiated state (Tinland et al, 1990); and it enhances the effects of both auxin and cytokinin on crown gall formation (Canaday et al, 1992).…”
Section: Introductionmentioning
confidence: 99%